KAJIAN INTERAKSI SOSIAL PONDOK PESANTREN TARBIYATUL QUR'AN AL-WARO DENGAN MASYARAKAT SEKITAR (STUDI KELURAHAN KARANGPANDAN, KECAMATAN JUWIRING, KABUPATEN KLATEN) - Annisa Cahyaningrum (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
This study examines the social interactions of the Tarbiyatul Qur’an al- Waro Islamic boarding school with the community around the lodge in Karangpandan, Juwiring, Klaten. This research is a qualitative research using descriptive methods. Data taken based on observation, interviews, and documentation. Data is then described and analyzed. This study focuses on social interaction in the community around the Tarbiyatul Qur’an al-Waro Islamic boarding school. This study found that the social interaction of the Tarbiyatul Qur’an al-Waro Islamic boarding school with the Karangpandan Village community was very good. And the community plays a role and fully contributes to every activity carried out by Islamic boarding schools both financially and powerfully.